Particularities of legal regulation of franchising relations under the usa legislation (problem statement) - Косінова, Д. С. (Право, 2019)
The article is devoted to studying the peculiarities of legal regulation of franchising relations under the legislation of the United States of America (hereinafter referred to as – the USA). In particular, the author analyzed several regulatory acts of such states as Delaware, California, Texas, carried out their comparative analysis with legislative acts of the federal level and made the corresponding conclusions.
Keywords: franchising; franchising relations; franchisee; USA legislation